Elements of Ecology - Smith, Thomas M author; Smith, Robert L (Boston : Pearson, 2012)
Elements of Ecology,8th Edition continues to explain ecological processes clearly and concisely, with a greater emphasis on the relevance of ecology to everyday life and the human impact on ecosystems. This dramatically revised edition discusses issues of human ecology throughout the text and provides a greater variety of opportunities for students to learn, practice, and develop quantitative and analytical skills. Current research examples and other content updates are supported by more than 200 redesigned, full-color illustrations, graphs, and tables. Also available with MasteringBiology® This title is also available with MasteringBiology, an online homework, tutorial, and assessment program that improves results by helping students quickly master concepts both in and outside the classroom. The book and MasteringBiology work together to create a classroom experience that enables students to succeed in biology and ecology courses. Note
Includes bibliography references; Index v.p.
Keywords: Biology; Ecology; Zoology